Görünen ceza, görünmeyen infaz: Türkiye’de ceza ve infaz politikaları ışığında hükme riayet - Akdeniz, Galma; Alpan, Arca (İstanbul Medipol Üniversitesi Hukuk Fakültesi Dergisi, 2019)
ABSTRACT: Prison population in Turkey has ballooned since 2000. At this time, prisons are overcrowded and full. Instead of developing a comprehensive crime and justice policy to address this issue, temporary regulatory patches have been used to relieve the immediate overcrowding, by playing with how sentences are executed. Through these changes adopted in the Law on the Execution of Sentences and its related bylaws, a substantive gap has opened between the sentences imposed by criminal courts, and those executed in actuality. As a result, we conclude that Turkey currently has two penal policies: The “visible” one, as reflected in the Penal Code and the sentences meted out by courts, and the “invisible” one which is the result of how those sentences are executed, which is hidden from the public view. In order to demonstrate the size of this gap and the extent of the lack of “truth in sentencing” under the current state of affairs, a number of crime vignettes are presented, showing what the meted and executed sentences would be in each case. Keeping these results in mind, we call for an open and comprehensive discussion on how crime and criminality should be addressed, while taking into account the realities of prison and rehabilitation management, in order to improve the transparency, predictability, and the efficiency of penal policies.
How administration of prison sentences in Turkey undermines the truth in sentencing
Keywords: Penal policy; Execution of sentences; Criminal justice; Amnesty; Crime; Prisons